Association between wet-bulb globe temperature and epilepsy: a space-time-stratified case-crossover study in Taiwan - Yu-Tzu Chang; Yu-Ting Lin; Bao-Ru Chuang; Wen-Hsuan Chuang; Bing-Fang Hwang; Chau-Ren Jung (Tropical Medicine and Health)
Abstract Background Epilepsy is a common neurological disorder characterized by an enduring predisposition to generate epileptic seizures, along with its neurobiological, cognitive, psychological, and social consequences. Although a few studies have assessed the associations of meteorological factors, such as temperature, atmospheric pressure, and relative humidity, with epilepsy, their findings remain inconsistent. In this study, we used the wet-bulb globe temperature (WBGT), an integrated heat stress index closely aligned with human thermal perception, to assess its associations with epilepsy risk. Methods This study employed a space–time-stratified case-crossover study design, analyzing 187,657 epileptic seizures recorded in emergency department visits in the Taiwan Health Insurance Research Database between 2007 and 2017. Daily WBGT values at individuals’ residential addresses were estimated using a 1-km resolution spatiotemporal model. The effects of an interquartile range (IQR) increase in WBGT on the day of epileptic seizures were compared to 3–4 reference days within the same month using conditional logistic regressions combined with distributed lag non-linear models (DLNMs). Results The lag-response relationship indicated a significant positive association between WBGT and epilepsy risk at lag 0 day (odds ratio [OR] = 1.083, 95% confidence interval [CI]: 1.061–1.105), whereas significant negative associations were observed at lag 1 and lag 2 day, suggesting a harvesting effect. The cumulative effect of heat persisted for 2 days. Additionally, the exposure–response relationship between WBGT and epilepsy at lag 0 day was linear, with no apparent threshold observed. Conclusion Our findings suggest that heat exposure may trigger epilepsy, resulting in short-term clustering of epilepsy cases. As precision medicine continues to gain prominence, incorporating precise heat stress indicator, such as WBGT, into individualized epilepsy management strategies may enhance patient care and seizure prevention.